Gambaran Kesehatan Gigi Mulut dan Jumlah Streptococcus Sp pada Anak Sindroma Down di Kecamatan Patrang dan Sumbersari Jember - Fairuz Subiantoro; Berlian Prihatiningrum; Niken Probosari (STOMATOGNATIC - Jurnal Kedokteran Gigi, 2022)
Down syndrome is a disorder that causes distinctive physical and mental disorders, causing a slower learning process than normal people. One of the consequences of these physical and mental limitations is the magnitude of dental and oral health problems. To check the state of oral hygiene, DMF-T and OHI-S examinations can be done. In addition, the presence of caries causes, such as Streptococcus sp can be a state of oral hygiene. This study aimed to examine the description of dental and oral health and the effect of the number of Streptococcus sp bacteria in saliva on the incidence of caries in children with Down syndrome at SLB Negeri Patrang, SLB C Taman Pendidikan and Asuhan (TPA) Sumbersari and SLB C Bintoro Regency. Jember. This study was a descriptive study with cross sectional design. This study was held at SLB Negeri Patrang, SLB C Bintoro, and SLB C TPA Sumbersari. This study showed there were differences to the caries incidence and dental hygiene of Down syndrome’s children at SLB Negeri Patrang, SLB C Bintoro, SLB C TPA Sumbersari. Besided it, there were significant differences between the DMF-T index and the colonies of Streptococcus sp, while there was no significant difference of oral hygiene down syndrome children in SLB Negeri Patrang, SLB C Bintoro, SLB C TPA Sumbersari. Briefly, this study showed that the number of Streptococcus sp colonies not frequently correlated to caries incidence and oral hygiene.